Impact of DDT on FPSO explosion risk assessment. Issue 1 (4th July 2014) - Hansen, Olav Roald; Martini, Remi; Choi, Jaewoong; Ryu, Yonghee
<x xml:space="preserve">Abstract</x> In recent explosion accidents on onshore petrochemical facilities, it has been concluded that a deflagration‐to‐detonation‐transition (DDT) took place, both with Liquefied Petroleum Gas (LPG) and gasoline vapor. DDT has also been observed in a number of large‐scale experiments. DDT leads to very high pressures (16–20 barg) and flame speeds (1, 600–2, 000 m/s) even outside congested regions and has a significant impact on the severity of the near‐field and far‐field explosion loads. It has not been generally accepted that DDT may be a threat at offshore petrochemical facilities and prediction tools have not been available. Thus, the potential effect of DDT is seldom considered. For Floating production, storage and offloading vessels (FPSOs), and even more Floating liquified natural gas vessels (FLNGs), due to larger dimensions and inventories, operators should be concerned that major explosion scenarios can lead to DDT phenomena. Recently, a DDT prediction parameter was implemented in the Computational Fluid Dynamics (CFD) model FLACS, and with model adjustments it is possible to calculate DDT and effect on explosion loads with good precision. A CFD‐based FPSO explosion study is presented evaluating DDT potential and impact. DDT will mainly be a concern for large cloud sizes, often larger than commonly considered for design accidental loads for an FPSO (10−4/year). Mitigation by separation walls is also evaluated. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 44–57, 2015